A Planning of Campus Environment Identification System for Students with Visual Impairments - Huang, Chih-Hong; Yu, Shu-Chuan (Discoveries in Agriculture and Food Sciences, 2014)
Orientations and movements affect the ability of blind people to independently act and live in the environment. The purpose of this research is to develop the guiding facility in campus for blind people by the architecture plans. Through observations at site, interviews, and cognition sketch maps, we found the blind people are easily lost at intersection. When they are lost, they are disorientated in the environment. The constructed cognition maps suddenly lost the functions. According to documents, through RFID (Radio Frequency Identification Technology), the real-time message can be transmitted in the environment. In this paper, the configuration for the barrier free environment in campus is developed with RFID technology based on the requirements of users. This can provide references to the environmental designers for the configuration of facility for guiding blind people in the public spatial environment.